Simulation of Light Naphtha Isomerization Process - Chuzlov V. A. Vyacheslav Alekseevich; Ivanchina E. D. Emilia Dmitrievna; Dolganov I. M. Igor Mikhailovich; Molotov K. V. Konstantin (2015, 2015)
Title screen